Using Option Prices to Infer Overpayments and Synergies in M&A Transactions - Barraclough, Kathryn; Robinson, David T.; Smith, Tom; Whaley, Robert E. (Review of Financial Studies, 2013)
[In this paper, we use call option prices to identify synergies and news from merger and acquisition (M&A) transaction announcements. We find that M&A announcements result in large and approximately equal gains to the bidder and the target on average, with the combined gains being large enough to justify the premium paid to target shareholders. On average, M&A announcements release good news about targets, but bad news about bidders. This suggests that market prices understate true synergy gains, and helps reconcile the generally negative market-based evidence on value-creation in takeovers with their continued prominence in everyday business strategy.]